2017
DOI: 10.1016/j.prnil.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Looking to the metabolic landscapes for prostate health monitoring

Abstract: Abnormal metabolism is a widely accepted biological signature of prostatic diseases, including prostate cancer and benign prostate hyperplasia. Recently accumulated epidemiological and experimental evidence illustrate that the metabolic syndrome, impaired mitochondrial function, and prostatic pathological conditions intersect. The perturbed metabolism and metabolic mediates influence key signaling pathways in various prostatic pathological conditions. This short review article aids to highlight recent findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Since the discovery of evidence presenting that perturbed metabolic pathways, such as oxidative phosphorylation, glycolysis, and fatty acid biosynthesis, can suppress cancer cell growth, cancer metabolism has become an emerging field [50][51][52]. In this study, a series of unbiased proteomics and consecutive functional experiments revealed that knocking-out CENPF impaired mitochondrial functioning and signaling activation that is required for PC growth and metastasis.…”
Section: Discussionmentioning
confidence: 88%
“…Since the discovery of evidence presenting that perturbed metabolic pathways, such as oxidative phosphorylation, glycolysis, and fatty acid biosynthesis, can suppress cancer cell growth, cancer metabolism has become an emerging field [50][51][52]. In this study, a series of unbiased proteomics and consecutive functional experiments revealed that knocking-out CENPF impaired mitochondrial functioning and signaling activation that is required for PC growth and metastasis.…”
Section: Discussionmentioning
confidence: 88%
“…As proposed in our previously published review articles, monitoring the changes in metabolic landscape, cholesterol, and sex hormones through metabolic profiling can be of immense benefit to patients 31 , 32 . Our urinary metabolomics data clearly suggests that sex differences should be considered in future laboratory and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of inflammation in BPH tissues has been reported in 43%–98% of samples, and the severity of inflammation may aggravate proportionally to prostate enlargement 3 . Increasing epidemiological and experimental evidence illustrated that the metabolic syndrome, weakened mitochondrial function, as well as prostatic pathological conditions intersect 4 . Mitochondria exert essential physiological functions that produce multifaceted links among nutrition, health, and disease, whereas mitochondrial dysfunction with the ensuing impairment of oxidative phosphorylation might be responsible for the pathophysiology of common conditions 5 .…”
Section: Introductionmentioning
confidence: 99%